2023
DOI: 10.1136/jitc-2023-006666
|View full text |Cite
|
Sign up to set email alerts
|

TP53gain-of-function mutation modulates the immunosuppressive microenvironment in non-HPV-associated oral squamous cell carcinoma

Yewen Shi,
Xiaoyong Ren,
Shaolong Cao
et al.

Abstract: BackgroundTP53, the most mutated gene in solid cancers, has a profound impact on most hallmarks of cancer. SomaticTP53mutations occur in high frequencies in head and neck cancers, including oral squamous cell carcinoma (OSCC). Our study aims to understand the role ofTP53gain-of-function mutation in modulating the tumor immune microenvironment (TIME) in OSCC.MethodsShort hairpin RNA knockdown of mutantp53R172Hin syngeneic oral tumors demonstrated changes in tumor growth between immunocompetent and immunodeficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…TP53, as the gene with the highest mutation frequency in human cancer, plays an important role in inducing cell apoptosis, aging, cell cycle arrest, and DNA damage repair, and is associated with increased chromosomal instability [42,43]. Previous studies have shown that TP53 mutations can increase the expression of relevant immune checkpoint molecules, and inhibit the in ltration of cytotoxic CD8 + T cells, leading to immunosuppressive states that induce macrophage polarization towards the M2 phenotype of TAMs, resulting in sustained tumor progression and a higher mutation frequency in high-risk groups [44]. TTN mutations can cause varied gene expression in cancers, boost tumor immune response, and increase susceptibility to immunotherapy [45].…”
Section: Discussionmentioning
confidence: 99%
“…TP53, as the gene with the highest mutation frequency in human cancer, plays an important role in inducing cell apoptosis, aging, cell cycle arrest, and DNA damage repair, and is associated with increased chromosomal instability [42,43]. Previous studies have shown that TP53 mutations can increase the expression of relevant immune checkpoint molecules, and inhibit the in ltration of cytotoxic CD8 + T cells, leading to immunosuppressive states that induce macrophage polarization towards the M2 phenotype of TAMs, resulting in sustained tumor progression and a higher mutation frequency in high-risk groups [44]. TTN mutations can cause varied gene expression in cancers, boost tumor immune response, and increase susceptibility to immunotherapy [45].…”
Section: Discussionmentioning
confidence: 99%
“…As for the underlying mechanisms, one hypothesis is that the mutant p53 could instigate the production of immunosuppressive cytokines while simultaneously suppressing proin ammatory factors. Shi et al found that the occurrence of TP53 mutations triggered a complex network of cytokine production, which obstructed the in ltration of cytotoxic CD8 + T cells while facilitating the accumulation of regulatory T cells (Tregs) and M2 macrophages within the oral squamous cell carcinoma (OSCC) tumor site 79 . Speci cally, the cytokine IFN-I 80 , IL6 81 and TGF-β 82 were reported to be responsive with TP53 mutations, hence in uencing tumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is a type of carcinoma affecting functional hepatocytes of epithelial origin (Feng et TP53 is a major tumor suppressor gene commonly mutated in many cancers (Ruijs et al 2010;Giacomelli et al 2018;Marei et al 2021). Mutation of this gene can result in both loss-of-function (Wang et al 2024) and gain-of-function effects (Shi et al 2023;Liu et al 2023). Studies have reported that mutations in speci c codons of TP53 can result in a mutant protein with a dominant negative effect on the wild-type protein, rendering the wild-type protein ineffective in its functions (Monti et al 2011).…”
Section: Introductionmentioning
confidence: 99%